2020
DOI: 10.3389/fpsyg.2020.01332
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Leader Behaviors With Innovation Requirements Improves Performance: An Experimental Study

Abstract: In this experiment, the effect of the alignment of leader behaviors with innovation requirements was investigated. A sample of N = 245 students participated in a laboratory experiment. Participants had to address either creativity or implementation requirements within a task and received a leadership manipulation in a video message. Results showed that the alignment of leader behaviors with innovation requirements led to improved performance. These findings contribute to the literature by addressing the specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 88 publications
(265 reference statements)
1
11
0
Order By: Relevance
“…A recent study that offers some support of our ideas is an experimental study by Gerlach, Heinigk et al (2020), who found that participants' task performance was positively predicted by opening behaviours when creativity was required, and positively predicted by closing behaviours when implementation was required. However, performance in this study was measured on different tasks and not in an organizational setting.…”
Section: Ambidextrous Leadership Idea Generation and The Later Stages Of Innovationmentioning
confidence: 52%
“…A recent study that offers some support of our ideas is an experimental study by Gerlach, Heinigk et al (2020), who found that participants' task performance was positively predicted by opening behaviours when creativity was required, and positively predicted by closing behaviours when implementation was required. However, performance in this study was measured on different tasks and not in an organizational setting.…”
Section: Ambidextrous Leadership Idea Generation and The Later Stages Of Innovationmentioning
confidence: 52%
“…Most previous research on ambidextrous leadership has used correlational study designs (e.g., Gerlach, Hundeling et al, 2020; Zacher et al, 2016), which may have resulted in inflated relationships due to common method variance. However, recent experimental evidence suggests that opening and closing leader behaviors influence follower behavior and performance, at least under some circumstances (Gerlach, Heinigk et al, 2020; Klonek et al, 2020). Specifically, an experimental study by Gerlach, Henigk et al (2020) examined the separate effects of opening and closing leader behaviors on innovation performance.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent experimental evidence suggests that opening and closing leader behaviors influence follower behavior and performance, at least under some circumstances (Gerlach, Heinigk et al, 2020; Klonek et al, 2020). Specifically, an experimental study by Gerlach, Henigk et al (2020) examined the separate effects of opening and closing leader behaviors on innovation performance. This study provides evidence that opening and closing leader behaviors impact innovative performance when creativity and implementation task requirements are aligned with leader behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that regard, it is important to note that process management differs from the construct of ambidextrous leadership that has a broader understanding of opening, closing, and alternating leader behaviors as being less instructional and instead also including inspiring and transformational components (e.g. Gerlach et al, 2020; Klonek et al, 2020).…”
Section: Discussionmentioning
confidence: 99%